2016
DOI: 10.9790/0853-1509088184
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Tadalafil and Tamsulosin as on therapy For Lower Urinary Tract Symptoms Due To Benign Hyperplasia of Prostate.

Abstract: Objectives: The U.S. Food and Drug Administration approved tadalafil in 2011 to treat the signs and symptoms of Lower Urinary Tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Shalaby., et al (2013) [19] found statistically significant difference in VAS scores in favour of Tamsulosin group (P = 0.00). Pawar and colleagues (2016)[20] also concluded with same result. For many patient's stent symptoms account for most of the morbidity associated with ureteroscopy.…”
supporting
confidence: 56%
“…Shalaby., et al (2013) [19] found statistically significant difference in VAS scores in favour of Tamsulosin group (P = 0.00). Pawar and colleagues (2016)[20] also concluded with same result. For many patient's stent symptoms account for most of the morbidity associated with ureteroscopy.…”
supporting
confidence: 56%